Counter-Clockwise Rotation of Maxillomandibular Complex and Customized Joint Reconstruction as a Single Stage Management for Facial Deformity in Temporomandibular Joint Ankylosis: A 2 Year Follow-Up. (20th July 2021) - Mehrotra, Divya; Yadav, Pradeep K; Katrolia, Ravi; Khan, Haaris
Study Design: A case report with 2 year follow up. Objective: The aim of this paper is to present a case of bilateral TMJ ankylosis with coexisting dentofacial deformity and occlusal cant, and 2 years follow-up evaluation for changes and relapse in the facial skeletal and airway. Methods: The patient was planned preoperatively by computer simulation for bilateral interposition arthroplasty and surgical jigs, coronoidectomy, detachment of masseter and medial pterygoid muscles from ramus, LeFort 1 osteotomy, temporary maxillomandibular fixation, counter-clockwise rotation of the maxillomandibular complex, maxillary fixation and iliac crest graft, reconstruction of bilateral TMJ with custom-made total joint prosthesis, dermal fat interposition in the joint, reattachment of muscles, maxillomandibular fixation, and active physiotherapy. Results: Average ramal length improved by 28.35 mm (81%) in the immediate postoperative and 25.6 mm (73.45%) at 2 years, showing 2.75 mm (4.4%) vertical bone resorption at the angle region. Point A advanced by 1.3 mm, but showed 4.5% horizontal relapse; Point B advanced by 10.2 mm, but showed 9.5% relapse at 2 years. Pogonion advanced by 26.3 mm (70%) but presented 7 mm (10.9%) horizontal relapse; and menton by 28.6 mm (89%) with 5.4 mm (8.9%) relapse at 2 years. The mean mandibular plane angle decreased by 33.5° (42%) after surgery and by 32° (40%) at 2 years. Pharyngeal airway increased by 49% after surgery and by 75.6% at 2 years follow-up. Conclusion: This computer simulated approach for the management of bilateral TMJ ankylosis with facial deformity and occlusal cant improves aesthetics, function and airway in a single surgery, thereby reducing the management cost and time, and deliver precise results.